Mobility Perspective in Anthropology of Policy: Case Studies Urban Policy in Indonesia - Haryo Kunto Wibisono; Semiarto Aji Purwanto (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
This article explores anthropological perspectives in public policy by using the central concept of policy mobility. Through this concept, we will show how policy resulting from the accumulation of knowledge, strength, and geographical imagination moves from one territory to another. The emphasis on forming policy ideas is different from policy studies from another perspective that looks at governance to shape the behavior of the people. We take the case of forming creative city ideas in Balikpapan, East Kalimantan to show mutation and hybridization of policies. We use ethnographic methods to collect data, supplemented by literature reviews on creative city policies. For decades, Balikpapan has been known as an extractive industrial city, especially in the mining and forestry sectors. Due to pressure from national and global environmentalists, exploration of natural resources must be limited, reducing urban productivity. Policymakers see the creative city as an opportunity to improve the city's economic life while maintaining the sustainability of the local natural and cultural environment.